2003
DOI: 10.1023/a:1025177411938
|View full text |Cite
|
Sign up to set email alerts
|

A model of mucopolysaccharidosis IIIB (Sanfilippo syndrome type IIIB): N‐acetyl‐α‐D‐glucosaminidase deficiency in Schipperke dogs

Abstract: Mucopolysaccharidosis III (MPS III) is characterized by lysosomal accumulation of the glycosaminoglycan (GAG) heparan sulphate (HS). In humans, the disease manifests in early childhood, and is characterized by a progressive central neuropathy leading to death in the second decade. This disease has also been described in mice (MPS IIIA and IIIB), dogs (MPS IIIA), emus (MPS IIIB) and goats (MPS IIID). We now report on dogs with naturally occurring MPS IIIB, detailing the clinical signs, diagnosis, histopathology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 33 publications
2
46
0
2
Order By: Relevance
“…Our data have demonstrated neuropathology in the spinal cord of MPS IIIB mice that is global in distribution with differential cell-type presentation, similar to that observed in previous studies in mice and dogs [4], [5]. While the lysosomal storage lesions are observed in a broad range of cell-types throughout the spinal cord, including neurons, microglia, oligodendrocytes, pericytes and ependymal cells, the neuronal targets are predominantly motor neurons in the ventral horn and autonomic neurons in the lateral horn of grey matter.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our data have demonstrated neuropathology in the spinal cord of MPS IIIB mice that is global in distribution with differential cell-type presentation, similar to that observed in previous studies in mice and dogs [4], [5]. While the lysosomal storage lesions are observed in a broad range of cell-types throughout the spinal cord, including neurons, microglia, oligodendrocytes, pericytes and ependymal cells, the neuronal targets are predominantly motor neurons in the ventral horn and autonomic neurons in the lateral horn of grey matter.…”
Section: Discussionsupporting
confidence: 90%
“…It is known that the lysosomal storage pathology of MPS IIIB is global throughout the CNS and neuropathology studies have focused predominantly on changes in the brain, though previous studies showed lysosomal storage lesions in all parts of the CNS in mice and dogs [4], [5]. Further, it is commonly accepted that in the brain, multiple factors contribute to the neuropathology, secondary to the primary pathology- the lysosomal storage of HS-GAGs [4], [6], [7], [8], [9], [10], [11], [12], [13], [14].…”
Section: Introductionmentioning
confidence: 99%
“…Characteristic pathologic changes are seen in the brain and other organs of MPS III patients, including lysosomal inclusions, cerebellar atrophy with loss of Purkinje cells [8], [9], [10], cortical and corpus callosum atrophy with white matter changes [11], [5], retinal pigmented epithelium (RPE) pigmentation loss, and photoreceptor degeneration [7], [12]. Usually symptom progression occurs over a decade starting around age 3–5.…”
Section: Introductionmentioning
confidence: 99%
“…MPS IIIb is observed in Schipperkes where the mutant allele is very prevalent (258,259,263). It is typically present in dogs around 2 years of age and leads to euthanasia prior to 5 years of age.…”
Section: Mps Iiibmentioning
confidence: 99%
“…Initial pathologic studies of Schipperkes showed that the major tissues affected in dogs (liver, kidney, CNS) were consistent with human. The most impressive finding in the Schipperkes with MPS IIIb was an almost complete loss of cerebellar Purkinje cells (263). Humans show varying degrees of cerebellar pathology leading to the belief that this may be a species sensitivity to HS accumulation seen in canines (263).…”
Section: Mps Iiibmentioning
confidence: 99%